Increase in coverage of pension system colombian (2012)
The need for changes in the general pension system (GPS) has become one of the main goals of the Colombian government since the pension reform of popular Law 100 of 1993. The high rate of elderly who don’t hold any income and the poor sustainability of the pension system have succeeded in increasing poverty levels, involving each of the Colombians because it affects directly and emphasized the social economic development of the country. Each of the mechanisms of the state is looking bulwark sustainable measures that achieve the goal of coverage where each of the Colombian-income seniors are contributing to a pension fund and create a financial cushion that allows for true credibility.